A full-featured efficient clustering mechanism for improving QoS in MANETs. (2018) - Marcel, Gatete; Kovalan, A.
Due to the dynamicity of MANET's topology and its infrastructureless nature, various problems arise from those inherent properties which degrade the QoS. Those negative issues are the energy constraints, problems related to broadcasting, high node mobility, unpartitioned network, and various challenges faced during the path discovery, route selection, packet scheduling and packet transmission processes, and security issues. To find an efficient solution to all those problems, in this paper, we propose a robust algorithm; Full-featured secure routing clustering algorithm with energy-aware and scheduling capabilities for highly increasing QoS in MANET (FSR-CAES), an efficient clustering technique which is a combination of numerous algorithms, each one containing one of the previously mentioned problems. The simulation results are provided with the NS-2 simulator varying the number of nodes and the evaluating parameters namely the routing overhead, packet delivery ratio, normalised routing load, and the average end-to-end delay while comparing the performance of our proposed scheme with neighbour coverage-based probabilistic rebroadcast (NCPR), a routing protocol specialised in providing high QoS in MANETs as it is efficient in reducing the routing overhead in the network. The outcomes prove that our proposed scheme outperforms NCPR for all the studied scenarios for small, medium, and large MANETs.